HADİS USÛLÜNDE ÇOCUK SAHÂBÎLERİN RİVÂYETİ MESELESİ - ERDİM, SIDIKA BETÜL (Fırat Üniveristesi, 2017)
Çocuk sahâbî kavramıyla, Allah Rasûlü'nü küçük yaşta idrak etmiş olan ve çocukluklarının belli bir dönemini Rasûlullah (a.s)'ın zamanında geçirmiş; fakat onun vefâtı sırasında yaşı çok büyük olmayıp hala çocukluk ya da ergenlik döneminde bulunmuş kişiler kastedilmektedir. Araştırmamızda bir çocuğa sahâbî demenin ölçüsünün ne olduğu, Allah Rasûlü'yle olan sohbetin niteliği ile ilintili olarak ele alınmıştır. Çocukların sahâbî vasfını kazandıktan sonra Allah Rasulü'nden rivâyette bulunmaları, rivâyet etme ehliyetini taşıyıp taşımadıkları, çocukların Allah Rasûlü'nden direkt yaptıkları rivâyetleri, hangi kanaldan almış oldukları inceleme alanımıza giren hususlardır. Klasik hadis usulü eserlerinde sahâbî vasfını kazanmayan çocuklar ile çocuk sahâbîlerin rivâyet niteliklerinin ayrı ayrı değerlendirildiği görülmektedir. Bu bağlamda konumuzla ilintili olan sahâbî mürseli, mürsel rivâyet, mevkûf ve maktu' hadis kavramlarına da yer verilmiştir. Anahtar Kelimeler: Rivâyet, Çocuk Sahâbî, Mürsel Hadis, Sahâbî Mürseli,Mevkûf

The term "child Companion" here refers to the people who comprehend the Prophet at a very young age and spent a certain period of childhood in the time of Prophet Muhammad but were not too old and were still at their childhood or adulthood during his death. In our study, the concept of referring to a child as a Companion is discussed in relation to the quality of his talks with the Prophet. These child Companions are analysed on issues like whether they reported Hadith after they acquired the companionship qualifications, or if they had the such qualities to report and on which channels they obtained their direct reports from the Prophet. In classical works of hadith metholody, it is seen that the qualities of hadith reports by the child Companions and by other children who don't have the qualification of companionship are evaluated seperately. In this context, relevant terms such as Mursal of the Companions, mursal narration, mawquf and maqtu' are also discussed. Keywords: Hadith Reports, Child Companion, Mursal Hadith, Mursal of The Companions, Mawquf.
The issue of hadith reporting by child companions in the methodology of hadith
Keywords: Din